Leukoreduction therapy in pediatric malignant pertussis: a systematic review - Melati Wijaya; Indra Ihsan; Rinang Mariko (Indonesian Pediatric Society, 2026)
Background Malignant pertussis (MP) in children is a severe form of pertussis characterized by hyperleukocytosis, which can be life-threatening and requires appropriate treatment to reduce mortality. Objective To review the effectiveness of available leukoreduction therapy modalities for pediatric MP. Methods A systematic literature review was performed in adherence to PRISMA guidelines. We searched MEDLINE (PubMed), Google Scholar, and ScienceDirect and included studies in English published from 2005 to 2025 which involved leukoreduction modalities such as exchange transfusion (ET), leukapheresis, extracorporeal membrane oxygenation (ECMO) with leukofiltration (ECMO-LF), and hydroxyurea (HU) plus supportive care on children aged 0-5 years with MP. Results Twenty articles were identified involving 241 cases of MP. The median age was 2 (range 0.4-19) months. White blood cell (WBC) reduction was 67-74% with ET (n=92), 65.2% with leukapheresis (n=6), 83% with ECMO-LF (n=5), and 23-70% with HU (n=9). In contrast to the other modalities, HU provided gradual reduction. Survival was significantly higher in the leukoreduction group (52.7%) compared to the non-leukoreduction group (32.6%) (P<0.01). WBC-stratified subgroup analysis demonstrated that patients with WBC ≥70,000/mm³ had a lower survival rate than those with WBC>50,000 to <70,000/mm³ (47.2% vs. 60.0%; P=0.048). Among patients with WBC ≥70,000/mm³, leukoreduction provided higher survival than did supportive care (55.2% vs. 14.3%; P=0.031; NNT=2.4). No significant difference in survival was observed in those with WBC >50,000/mm3 to <70,000/mm³ receiving leukoreduction vs. supportive care (57.1% vs. 66.7%; P=0.626). Conclusion Early identification of mortality risk factors and prompt management prior to organ dysfunction are essential for reducing mortality. Leukoreduction therapy should be considered for patients with WBC ≥70,000/mm³. Hydroxyurea may serve as an alternative non-invasive therapeutic option.